Fatty acid composition and cyclopropene fatty acid content of China-chestnuts (Sterculia monosperma, ventenat) - Berry, S.K. (Wiley, 1982)
The China-chestnuts (Sterculia monosperma, Ventenat) were examined for their fatty acid composition by gas liquid chromatography, infrared and nuclear magnetic resonance spectroscopy. The oil in nuts contained cyclopropene fatty acids (CPFA) determined as silver nitrate derivatives of their esters. The values (area %) for the major fatty acids as methyl esters were 23.47% C16:0, 1.25% C16:1, 2.56% C18:0, 24.89% C18:1, 18.24% C18:2, 5.40% dihydrosterculic, 3.21% C18:3 + C20:0 and 19.15% sterculic. The proportion of CPFA in the oil did not decrease upon cooking the nuts.